Il pensiero patristico bizantino dei secoli IV-VIII e l'ambiente - IVANOVIC, Filip (Byzantina Symmeikta, 2021)
The article situates itself within the debate on ecological issues by emphasizing the importance of philosophical and theological approach to the questions at stake, and focusing on the contributions of Byzantine thought, which has been rather neglected in this context. With this in mind, the article offers a panoramic view of several Byzantine authors’ ideas on the environment and the relationship between human beings and the rest of the creation. By examining the thought of Maximus the Confessor, Dionysius the Areopagite, John Damascene, and John Chrysostom the author highlights their views on deification, unity of creation, and environmental/animal ethics in order to conclude that the mainstream Byzantine vision of nature was not its exploitation, but affirmation of the created world and crucial responsibility of human beings in it.